E-Learning: Future of Education - SUMIT GOYAL (Journal of Education and Learning (EduLearn), 2012)
This paper highlights the significance of E-learning in modern education and discusses its technical aspect, market, pros and cons, comparison with instructor led training and possibility of weather E-learning will replace the old classroom teaching. Presently the concept of E-learning is becoming very popular as the numbers of internet savvy users are increasing. E-learning gives the advantage of 24x7 and 365 days a year round access as compared to Instructor-Led Training, which is one time class that must be scheduled. E-learning is cost effective as course content once developed could be easily used and modified for teaching and training. E-learning also provides students freedom from carrying heavy school bags and stop cutting of trees for the sake of paper, pencil and rubber. E-learning is the future of education as it is interactive, interesting and entertaining way of learning, and will soon replace the paper books in the form of touch screen tablets.